Streptococcus constellatus Causing Septic Thrombophlebitis of the Right Ovarian Vein with Extension into the Inferior Vena Cava - Abdallah Haidar; Amy Haddad; Amir Naqvi; Ngozi U. Onyesoh; Rushdah Malik; Michael Williams (Case Reports in Infectious Diseases)
Introduction. Streptococcus constellatus collectively with Streptococcus anginosus and Streptococcus intermedius constitute the Streptococcus anginosus (formerly Streptococcus milleri) group. Though they are commonly associated with abscesses, bacteremia with subsequent septic thrombophlebitis is extremely rare, and resulting mortality is infrequent. Case Presentation. We report a case of a previously healthy 60-year-old African American female who presented with Streptococcus constellatus bacteremia associated with septic thrombophlebitis to the right ovarian vein extending into the inferior vena cava. She was urgently treated with antibiotics and anticoagulation. Conclusion. Septic thrombophlebitis has a clinical presentation that is often misleading. Therefore, a high clinical index of suspicion and the use of appropriate imaging modalities (computed tomography) are essential in recognizing and confirming this diagnosis. Prompt treatment is warranted. Surgical thrombectomies have been successfully replaced by a combination of antibiotics and anticoagulation therapy.